When silence sings [large type] - Thomas, Sarah Loudin (Thorndike Press large print Christian historical fiction, 2020)
"Colman Harpe works for the C&O in the Appalachian rail town of Thurmond, West Virginia, but he'd rather be a preacher and lead his own congregation. When a member of the rival McLean clan guns down his cousin and the clan matriarch, Serepta McLean, taunts the Harpes by coming to a tent revival in their territory, Colman chooses peace over seeking revenge with the rest of his family. Colman, known for an unnaturally keen sense of hearing, is shocked when he hears God tell him to preach to the McLeans. A failed attempt to run away leaves Colman sick and suffering in the last place he wanted to be--McLean territory. Nursed by herbalist Ivy Gordon--a woman whose birthmark has made her an outcast--he's hindered in his calling by Serepta's iron grip on the region and his uncle's desire to break that grip. But appearances can be deceiving, and he soon learns that the face of evil doesn't look like he expected"--